One Radius Theorem Harmonic Function Theory - ALEXIOU, DIMITRA (IJRDO -JOURNAL OF MATHEMATICS, 2019)
The present paper deals with the study of harmonic and analytical functions. It deals with well-known and powerful theorems of the Complex Analysis and has as its central theme the One-Radius Theorem, somehow reversing the Mean Value theorem of harmonic functions. These considerations are set out in Mark A. Pinsky’s article [ Mean Values and the Maximum Principle: A Proof in Search of More Theorems ].